Ergonomic Risk Assessment For Working Posture In Manufacturing Industry Using Cmdq - Farah Izzatie, Abu Bakar (2025)
In the last one or two decades, there has been increasing concern in the assessment of ergonomics risk to working posture in manufacturing Industry. This study looks at ergonomic risk assessment for working postures in the manufacturing business, specifically detecting and analysing musculoskeletal diseases (MSDs) among workers. The study used the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) to analyse ergonomic hazards and their association with working postures. The literature study found that incorrect working postures have a substantial role in work-related MSDs, impacting employee health and productivity. Previous research has shown that factory workers are more likely to develop MSDs as a result of uncomfortable postures,repetitive actions and extended static situations. The literature study found that incorrect working postures have a substantial role in work-related MSDs, impacting employee health and productivity. Previous research has shown that factory workers are more likely to develop MSDs as a result of uncomfortable postures, repetitive actions, and extended static situations. The research gap identified was the need for comprehensive ergonomic evaluations tailored to specific operating scenarios. The research gap identified was the need for comprehensive ergonomic evaluations tailored to specific operating scenarios. The technique used a cross-sectional comparative design, with 52 operators from Vacuumschmelze Sdn. Bhd. (M) in Pekan. Data was collected using the CMDQ and demographic questionnaires, and statistical analysis was carried out using SPSS. The study looked at the ergonomic hazards connected with working postures and how they relate to musculoskeletal pain. The research gap identified was the need for comprehensive ergonomic evaluations tailored to specific operating scenarios. The results revealed substantial gender variations in musculoskeletal pain patterns. Female workers reported higher levels of pain in the lower back (3.85), upper back (3.64), and right shoulder (3.28), whereas male workers were most uncomfortable in the lower back (2.50), shoulders (2.25), and neck (2.08). Twisting was recognised as the most prevalent working position (67.3%), followed by overhead reaching (13.5%), sitting, and lifting(9.6%).The research gap identified was the need for comprehensive ergonomic evaluation tailored to specific operating scenarios. The research gap identified was the need for comprehensive ergonomic evaluations tailored to specific operating scenarios. The study found a modest positive association (0.345) between working postures and CMDQ scores, suggesting that poor postures are related with higher musculoskeletal discomfort. The findings emphasise the significance of establishing complete ergonomic controls and treatments to decrease the incidence of MSDs in manufacturing settings, with a focus on gender-specific patterns of discomfort.